America's Colony : the Political and Cultural Conflict between the United States and Puerto Rico. - Malavet, Pedro A. (Critical America., 2004)
The precise legal nature of the relationship between the United States and the people of Puerto Rico was not explicitly determined in 1898 when the Treaty of Paris transferred sovereignty over Puerto Rico from Spain to the United States. Since then, many court cases, beginning in 1901, have been instrumental in defining this delicate relationship. While the legislation has clearly established the nonexistence of Puerto Rican nationhood and lack of independent Puerto Rican citizenship, the debate over Puerto Rico's status continues to this day. Malavet offers a critique of Puerto Rico's current.